Coverage Guided Multiple Base Choice Testing - Tuğlular, Tuğkan; Tuğlular, Tuğkan; Leblebici, Onur (IEEE, 2020)
A coverage guided input domain testing approach is presented with a feedback loop-controlled testing workflow and a tool is developed to support this workflow. Multiple base choices coverage criterion (MBCC) is chosen for systematic unit test generation in the proposed approach and branch coverage information is utilized as feedback to improve selection of bases, which results in improved branch coverage. The proposed workflow is supported with the tool designed and developed for coverage guided MBCC-based unit testing.
20th IEEE International Conference on Software Quality, Reliability, and Security (QRS) -- DEC 11-14, 2020 -- Macau, PEOPLES R CHINA -- IEEE, IEEE Comp Soc, IEEE Reliabil Soc
Keywords: Unit testing; Input domain testing; Multiple base choices coverage criterion; Branch coverage criterion; Feedback guided testing